Beyond humanism: philosophical essays on environmental ethics - Varghese, Saji (Published for Deptartment of Philosophy, Lady Keane College, Shillong by Concept Publishing Company, 2014)
Papers presented at the National Seminar on the theme 'Environmental Ethics in Tribal Societies: with Special Reference to North-East India', organized by the Department of Philosophy, Lady Keane College during 21-22 November 2012